Lack of spacing effects during piano learning. - Melody Wiseheart; Annalise A D'Souza; Jacey Chae (PLoS ONE, 2017)
Spacing effects during retention of verbal information are easily obtained, and the effect size is large. Relatively little evidence exists on whether motor skill retention benefits from distributed practice, with even less evidence on complex motor skills. We taught a 17-note musical sequence on a piano to individuals without prior formal training. There were five lags between learning episodes: 0-, 1-, 5-, 10-, and 15-min. After a 5-min retention interval, participants' performance was measured using three criteria: accuracy of note playing, consistency in pressure applied to the keys, and consistency in timing. No spacing effect was found, suggesting that the effect may not always be demonstrable for complex motor skills or non-verbal abilities (timing and motor skills). Additionally, we taught short phrases from five songs, using the same set of lags and retention interval, and did not find any spacing effect for accuracy of song reproduction. Our findings indicate that although the spacing effect is one of the most robust phenomena in the memory literature (as demonstrated by verbal learning studies), the effect may vary when considered in the novel realm of complex motor skills such as piano performance.